The Influence of Sharia Financial Literacy, Risk Perception, and Social Influence on Sharia Financial Inclusion of Gen Z: The Role of Interest Mediation - Ridho Alamsyah; Suhardi, Suhardi; Effendi Sugianto (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study analyzes the role of interest mediation in the relationship between Islamic financial literacy, risk perception, and social influence on Islamic financial inclusion in Generation Z. This study uses a quantitative approach with a survey method of 310 Gen Z respondents in Bangka Belitung. The analysis was conducted using Structural Equation Modeling (SEM) to test the relationship between variables, including the role of interest mediation in encouraging Islamic financial inclusion. The results of the study show that interest plays a significant mediator in the relationship between Islamic financial literacy and Islamic financial inclusion. Islamic financial literacy has a positive impact on interest, which in turn increases Islamic financial inclusion. However, risk perception negatively impacts interests, which hinders Islamic financial inclusion. Conversely, social influence has a direct positive impact on Islamic financial inclusion without the need to be mediated by interest. The implications of this study show the need for Islamic financial literacy education in the form of interactive digital and product transparency to reduce risk perception. In addition, the use of social influence through communities and technology-based incentives can increase interest in Islamic financial products.